CYCLICAL DYNAMICS OF TRANSPORT PRICING POLICY - T. Gainochenko (Вестник университета)
The article presents a periodization of the transport pricing policy in Russia, taking into account the dynamic properties of the world-system economic processes. The analysis of the main approaches to the periodization of the transport pricing policy is undertaken, main directions of it development are given.